Comparative genomics reveals cotton‐specific virulence factors in flexible genomic regions in Verticillium dahliae and evidence of horizontal gene transfer from Fusarium. Issue 2 (30th October 2017) - Chen, Jie‐Yin; Liu, Chun; Gui, Yue‐Jing; Si, Kai‐Wei; Zhang, Dan‐Dan; Wang, Jie; Short, Dylan P. G.; Huang, Jin‐Qun; Li, Nan‐Yang; Liang, Yong; Zhang, Wen‐Qi; Yang, Lin; et al.
Summary: Verticillium dahliae isolates are most virulent on the host from which they were originally isolated. Mechanisms underlying these dominant host adaptations are currently unknown. We sequenced the genome of V. dahliae Vd991, which is highly virulent on its original host, cotton, and performed comparisons with the reference genomes of JR2 (from tomato) and VdLs.17 (from lettuce). Pathogenicity‐related factor prediction, orthology and multigene family classification, transcriptome analyses, phylogenetic analyses, and pathogenicity experiments were performed. The Vd991 genome harbored several exclusive, lineage‐specific (LS) genes within LS regions (LSRs). Deletion mutants of the seven genes within one LSR (G‐LSR2) in Vd991 were less virulent only on cotton. Integration of G‐LSR2 genes individually into JR2 and VdLs.17 resulted in significantly enhanced virulence on cotton but did not affect virulence on tomato or lettuce. Transcription levels of the seven LS genes in Vd991 were higher during the early stages of cotton infection, as compared with other hosts. Phylogenetic analyses suggested that G‐LSR2 was acquired from Fusarium oxysporum f. sp. vasinfectum through horizontal gene transfer. Our results provide evidence that horizontal gene transfer from Fusarium to Vd991 contributed significantly to its adaptation to cotton and may represent a significant mechanism in the evolution of an asexual plant pathogen.